2021
DOI: 10.1021/acsabm.1c00238
|View full text |Cite
|
Sign up to set email alerts
|

Nanoceutical Fabric Prevents COVID-19 Spread through Expelled Respiratory Droplets: A Combined Computational, Spectroscopic, and Antimicrobial Study

Abstract: Centers for Disease Control and Prevention (CDC) warns the use of one-way valves or vents in face masks for potential threat of spreading COVID-19 through expelled respiratory droplets. Here, we have developed a nanoceutical cotton fabric duly sensitized with non-toxic zinc oxide nanomaterial for potential use as a membrane filter in the one-way valve for the ease of breathing without the threat of COVID-19 spreading. A detailed computational study revealed that zinc oxide nanoflowers (ZnO NFs) with almost two… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 71 publications
0
21
0
Order By: Relevance
“…Furthermore, another molecular docking analysis about the interaction between the adhesion proteins of the SARS-CoV-2 virus and ZnO nanostructures is presented by Adhikari et al [138] . In this work, the authors determined that the interaction between the spike protein of SARS-CoV-2 and the ACE-2 receptor is comparable in energy values, with that experienced between the spike adhesion protein of the virus and the surface of both 0D spherical NPs and the 〈1 0 0〉, 〈1 0 1〉 and 〈0 0 2〉 crystal faces of 2D ZnO nanostructures.…”
Section: Antimicrobial Activity Of Zn-based Materials For Covid-19 Di...mentioning
confidence: 99%
“…Furthermore, another molecular docking analysis about the interaction between the adhesion proteins of the SARS-CoV-2 virus and ZnO nanostructures is presented by Adhikari et al [138] . In this work, the authors determined that the interaction between the spike protein of SARS-CoV-2 and the ACE-2 receptor is comparable in energy values, with that experienced between the spike adhesion protein of the virus and the surface of both 0D spherical NPs and the 〈1 0 0〉, 〈1 0 1〉 and 〈0 0 2〉 crystal faces of 2D ZnO nanostructures.…”
Section: Antimicrobial Activity Of Zn-based Materials For Covid-19 Di...mentioning
confidence: 99%
“…To assess the SARS-CoV-2 antiviral activity of a product, scientists commonly utilize HCoV-229E as a substitute for the SARS-CoV-2 virus. 25 This is mostly owing to the fact that access to a biosafety level 3 facility (which is required to handle the SARS-CoV-2 virus) is both expensive and limited. HCoV-229E, on the other hand, only requires a biosafety level 2 laboratory, which significantly lowers the cost of studies and is readily available at uOttawa.…”
Section: Resultsmentioning
confidence: 99%
“… 28 During the preparation of our manuscript, two manuscripts reported the virucidal effect of a Ag NP solution and a Ag NP-impregnated polycotton fabric against SARS-CoV-2. 29 , 30 Besides, metal-oxide NPs, zinc oxide (ZnO) 22 , 24 , 25 and copper oxide (CuO) 23 , 26 NPs, have also shown antiviral and antibacterial effectiveness. On the other hand, researchers from the University of Arizona applied a proprietary antimicrobial surface coating made of a quaternary ammonium polymer on all hard and soft surfaces in selected medical units at a hospital and tested its efficacy against the human coronavirus 229E (HCoV-229E), which is similar in structure and genetics to SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…Another recent study presented a nanoceutical cotton fabric filter coated with ZnO nanoflowers (NFs) for potential use as a one-way valve membrane with improved breathability for controlling the spread of COVID-19 infection. 43 An antimicrobial analysis performed with Pseudomonas aeruginosa (model SARS-CoV-2 mimic) revealed enhanced antimicrobial efficacy of the product. An in-depth computational study has shown that ZnO NFs with two-dimensional petals display the ability to confine SARS-CoV-2 spike proteins.…”
Section: Nanostructured Antiviral Filtersmentioning
confidence: 99%